2015
DOI: 10.1007/s00359-015-0994-7
|View full text |Cite
|
Sign up to set email alerts
|

Motion cues improve the performance of harnessed bees in a colour learning task

Abstract: The proboscis extension conditioning (PER) is a successful behavioural paradigm for studying sensory and learning mechanisms in bees. Whilst mainly used with olfactory and tactile stimuli, more recently reliable PER conditioning has been achieved with visual stimuli such as colours and looming stripes. However, the results reported in different studies vary quite strongly, and it remains controversially discussed how to best condition visual PER. It is particularly striking that visual PER leads to more limite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 38 publications
1
24
0
Order By: Relevance
“…In the present study, we showed that restrained workers of the Western honey bee Apis mellifera carnica with intact antennae were capable of learning and discriminating between two monochromatic lights by using the PER paradigm. Whereas early studies stated that visual PER conditioning is only successful when the bee's antennae were ablated, recent studies revealed different results (Balamurali et al, 2015;Dobrin and Fahrbach, 2012;Jernigan et al, 2014;Lichtenstein et al, 2015;Riveros and Gronenberg, 2012). The present study provides further evidence that antennal deprivation is not necessary for successful color learning in restrained honey bees.…”
Section: Discussionsupporting
confidence: 41%
See 2 more Smart Citations
“…In the present study, we showed that restrained workers of the Western honey bee Apis mellifera carnica with intact antennae were capable of learning and discriminating between two monochromatic lights by using the PER paradigm. Whereas early studies stated that visual PER conditioning is only successful when the bee's antennae were ablated, recent studies revealed different results (Balamurali et al, 2015;Dobrin and Fahrbach, 2012;Jernigan et al, 2014;Lichtenstein et al, 2015;Riveros and Gronenberg, 2012). The present study provides further evidence that antennal deprivation is not necessary for successful color learning in restrained honey bees.…”
Section: Discussionsupporting
confidence: 41%
“…More than 60 years ago, Kuwabara (1957) conducted the first study of visual PER conditioning to investigate color learning of restrained honey bees and concluded that visual PER conditioning is only successful when bees are deprived of their antennae. Several studies confirmed his observation (Hori et al, 2006;Mota et al, 2011;Niggebrugge et al, 2009); but recently, other studies have shown successful conditioning of a visual stimulus with a sucrose reward using the PER in intact honey bees (Balamurali et al, 2015;Dobrin and Fahrbach, 2012;Jernigan et al, 2014) and bumble bees (Lichtenstein et al, 2015;Riveros and Gronenberg, 2012). However, at least for the Western honey bee, the performance level reached in restrained individuals with intact antennae was significantly lower than that achieved with olfactory conditioning (Dobrin and Fahrbach, 2012) or conditioning was only successful in combination with olfactory (Mota et al, 2011) or motion cues (Balamurali et al, 2015).…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…The methodology used here proved to be equally effective in conditioning antennae-deprived and intact harnessed bees to a visual differential task. After adapting (in different ways) previously published protocols for conditioning intact harnessed bees to visual stimuli (Dobrin and Fahrbach, 2012;Jernigan et al, 2014;Balamurali et al, 2015), we believe that some parameters were important to reach this goal in our laboratory: (i) complete darkness of the conditioning environment; (ii) large size and lateral presentation of the visual stimuli; and (iii) inclination of the bee body at 45 deg. Although these seemed to be important parameters for the success of our classical conditioning protocol, further controlled studies are necessary to understand how and to what extent they modulate appetitive visual learning in harnessed honeybees.…”
Section: Appetitive Visual Conditioning In Harnessed Honeybeesmentioning
confidence: 99%
“…It has proven difficult, however, to achieve successful conditioning of color stimuli with rewards or punishment in harnessed honey bees. Differential conditioning with a reward-paired color stimulus and a non-rewarded color stimulus resulted in moderate learning rates when the antennae were ablated (Kuwabara, 1957; Hori et al, 2006, 2007; Niggebrugge et al, 2009), when the bee was able to turn her head easily (Dobrin and Fahrbach, 2012) or when the color stimulus was combined with movement (Balamurali et al, 2015). Colored light, however, has been used successfully as a context for olfactory learning in PER when presented as an occasion-setter (Mota et al, 2011) or in a reinstatement paradigm (Plath et al, 2012).…”
Section: Introductionmentioning
confidence: 99%